2006
DOI: 10.1038/sj.sc.3101998
|View full text |Cite
|
Sign up to set email alerts
|

Maximal static mouth respiratory pressure in spinal cord injured patients: correlation with motor level

Abstract: Study design: Transversal. Objectives: The few studies concerning maximal static mouth respiratory pressures in patients with spinal cord lesions suggest a marked reduction. We studied the correlation of these parameters with the motor level of injury. Setting: Rehabilitation Center, Brası´lia/DF, Brazil. Methods: One hundred and thirty-one patients with traumatic spinal cord injury (C4-L3) were recruited. The participants were assessed by standard spirometry and maximal static mouth respiratory pressure. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Our study suggests that inspiratory muscle training at low loads has a positive effect in quadriplegic patients, since the initial values were lower than those predicted, whereas those obtained after 8 weeks of training were higher than the baseline values and showed no significant differences in relation to the predicted values, suggesting a trend towards normality after the specific training. These lower baseline values are in accordance with the findings of a study (23) showing that quadriplegic patients with injuries to the upper cervical spine (at C4 or C5) presented with the lowest values of MIP, MEP and FVC. It is important to note that the protocol that we used (low load muscle training) is an easy-to-perform exercise, which favors adherence to treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Our study suggests that inspiratory muscle training at low loads has a positive effect in quadriplegic patients, since the initial values were lower than those predicted, whereas those obtained after 8 weeks of training were higher than the baseline values and showed no significant differences in relation to the predicted values, suggesting a trend towards normality after the specific training. These lower baseline values are in accordance with the findings of a study (23) showing that quadriplegic patients with injuries to the upper cervical spine (at C4 or C5) presented with the lowest values of MIP, MEP and FVC. It is important to note that the protocol that we used (low load muscle training) is an easy-to-perform exercise, which favors adherence to treatment.…”
Section: Discussionsupporting
confidence: 81%
“…However, various factors can influence MIP and MEP results, (4)(5)(6)(7) and the value of MIP as an index of inspiratory power has been questioned. …”
mentioning
confidence: 99%
“…(2,3) The traditional investigations used in SCI patients are spirometry and determination of lung volumes. However, various factors can influence MIP and MEP results, (4)(5)(6)(7) and the value of MIP as an index of inspiratory power has been questioned. (6) One alternative is determination of sniff nasal inspiratory pressure (SNIP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, there was a valid argument suggesting that severity or completeness of the injury might playa role on pulmonary dysfunction after SCI. The results from a large transversal study in chronic spinal cord injured patients 175 revealed that there is a positive correlation between maximal respiratory pressures and level of the injury only in the motor complete SCI (AIS grades A and B). However, this was not the case for the motor incomplete SCI group (AIS grade C-D).…”
Section: Discussionmentioning
confidence: 99%